Limits of Babinet’s principle for solid and hollow plasmonic antennas - Horák, Michal; Křápek, Vlastimil; Hrtoň, Martin; Konečná, Andrea; Ligmajer, Filip; Stöger-Pollach, Michael; Šamořil, Tomáš; Paták, Aleš; Édes, Zoltán; Metelka, Ondřej; Babocký, Jiří; Šikola, Tomáš (Springer Nature, 2019)
We present an experimental and theoretical study of Babinet’s principle of complementarity in plasmonics.We have used spatially-resolved electron energy loss spectroscopy and cathodoluminescence to investigate electromagnetic response of elementary plasmonic antenna: gold discs and complementary disc-shaped apertures in a gold layer. We have also calculated their response to the plane wave illumination. While the qualitative validity of Babinet’s principle has been confirmed, quantitative differences have been found related to the energy and quality factor of the resonances and the magnitude of related near fields. In particular, apertures were found to exhibit stronger interaction with the electron beam than solid antennas, which makes them a remarkable alternative of the usual plasmonic-antennas design. We also examine the possibility of magnetic near field imaging based on the Babinet’s principle.

We present an experimental and theoretical study of Babinet’s principle of complementarity in plasmonics.We have used spatially-resolved electron energy loss spectroscopy and cathodoluminescence to investigate electromagnetic response of elementary plasmonic antenna: gold discs and complementary disc-shaped apertures in a gold layer. We have also calculated their response to the plane wave illumination. While the qualitative validity of Babinet’s principle has been confirmed, quantitative differences have been found related to the energy and quality factor of the resonances and the magnitude of related near fields. In particular, apertures were found to exhibit stronger interaction with the electron beam than solid antennas, which makes them a remarkable alternative of the usual plasmonic-antennas design. We also examine the possibility of magnetic near field imaging based on the Babinet’s principle.
Limits of Babinet’s principle for solid and hollow plasmonic antennas
Keywords: energy-loss spectroscopy; optical-excitations; energy-loss spectroscopy; optical-excitations